2019
DOI: 10.1021/acs.chemmater.9b02199
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Poly(Heptazine Imides): A Light-Storing Carbon Nitride Material for Dark Photocatalysis

Abstract: Solving the structure of carbon nitrides has been a long-standing challenge due to the low crystallinity and complex structures observed within this class of earth-abundant photocatalysts. Herein, we report on two-dimensional layered potassium poly(heptazine imide) (K-PHI) and its proton-exchanged counterpart (H-PHI), obtained by ionothermal synthesis using a molecular precursor route. We present a comprehensive analysis of the in-plane and three-dimensional structure of PHI. Transmission electron microscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
360
4
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(389 citation statements)
references
References 43 publications
22
360
4
3
Order By: Relevance
“…S2a †). 20,21 The valence band maximum (VBM) in K-PHI determined by ultraviolet photoelectron spectroscopy (UPS) is located at $2.5 V ( Fig. S2e †).…”
Section: Resultsmentioning
confidence: 99%
“…S2a †). 20,21 The valence band maximum (VBM) in K-PHI determined by ultraviolet photoelectron spectroscopy (UPS) is located at $2.5 V ( Fig. S2e †).…”
Section: Resultsmentioning
confidence: 99%
“…While in the former heptazine units are connected by amine bridges, in PHI the heptazine units are linked by deprotonated imides, whose charge is counterbalanced by metal cations introduced by the salt template . The negatively charged nitrogen sites not only remarkably enhance the conductivity of the material, but also efficiently host various metals as countercations, yielding an excellent dispersion and periodicity within the structure . Furthermore, PHI can host different metal ions in its structure, introduced during PHI formation or via post modification, i.e., ion exchange, and is therefore a promising material for developing novel transition metal–N x catalysts.…”
Section: Amount Of Cobalt In Phi‐co and Corresponding Weight Percentamentioning
confidence: 99%
“…acid treated K‐PHI, H‐PHI) on the other hand showed ca. 38 times higher activity in HER compared to K‐PHI …”
Section: Application Of Ionic Carbon Nitrides In Photocatalysismentioning
confidence: 99%
“…Lotsch et al. solved the structure of K‐PHI using transmission electron microscopy, while 13 C‐ 15 N 2D HETCOR spectrum confirmed that negative charge is localized at the deprotonated imide bridge between neighboring heptazine units . Furthermore, X‐Ray photoelectron spectroscopy (XPS) can be used to confirm the presence of deprotonated nitrogen atoms in the structure of K‐PHI as a signal at 396.6 eV in N 1s spectrum .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation